Decision Support System for Determining the Level of Employee Salary Increase in CV. Hera Citra Abadi by Using the Simple Additive Weghtting (SAW) Method - Suryatmo Sijabat (Institute of Computer Science, 2019)
In accordance with the regulations determined by the office to obtain a promotion, criteria are needed to determine who will be elected to receive promotion. Job promotion is carried out with the aim of providing feedback on the performance produced by a civil servant for a certain period. To help determine in applying someone who deserves to be promoted his position for Decision Support Systems is to use the Fuzzy Multi Attribute Decision Making (FMADM) model. In this study a case was raised, namely looking for the best alternative based on predetermined criteria using the Simple Additive Weighting (SAW) method to calculate the FMADM model in that case. Fuzzy is used using a fuzzy system rule that is fuzzification, inference and deffuzification. This FMADM model was chosen because it is able to select the best alternative from a number of intended alternatives, namely those who have the right to choose employees to be promoted in accordance with the specified criteria. The research was conducted by looking for weight values ​​for each attribute, then a ranking process was carried out that would determine the optimal alternative, namely the best civil servants.